PENGGUNAAN METODE MODELLING WRITING MENINGKATKAN KEMAMPUAN MENULIS TEKS RECOUNT SISWA KELAS X DI SMAN 1 TUBAN TAHUN PELAJARAN 2017/2018 - Wilujeng Rina Astuti (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
English curriculum 2013 for SMA and MA states that learning English aims to develop students competence to communicate in English both orally and written. It refers to the competence of mastering genre, understanding and producing some kinds of text, including recount text. In fact, students find some difficulties in digging their ideas and formulate them with sufficient vocabulary to construct the text as generic structure and language features. The research is aimed at improving student’s writing skills through modelling writing. The research employed a Classroom Action Research (CAR), and it was carried out on October 2017 to June 2018 at SMA Negeri 1 Tuban with 36 students of class X taken as samples. Document analysis, test and semi-structure interview were carried out to collect data. Questionnaires were given to the students, and semi-structured interview were given to the students, and with the qualitative technique and document analysis for analyzing the data obtained. The study was conducted in two cycles each consisting of four steps; planning, acting, observing, and reflection. In cycle 1, The modeling of writing by the teacher at front of the class follow engagement via writing activities: word level, sentence level and writing at the whole level. In cycle 2, the students have to as same actions as the first cycle. The result of research indicated that students have strongly agreed to the implementation of the modeling writing since learning process run more joyful and helping the student to improve their English writing skills and construct the text more easily both in group and individually.